Contralateral Renal Cell Carcinoma Ureteric Metastases Can Arise on Tyrosine Kinase Adjuvant Therapy and Be Effectively Treated by Endoscopic Laser Excision and Ablation - Sarah L. Reid; Nikolas J. Arestis; Craig McIlhenny; Gavin W. A. Lamb (Case Reports in Urology)
Renal cell carcinoma (RCC) uncommonly metastasizes to the ureter and rarely to the contralateral ureter. We describe the presentation of 2 successive contralateral ureteric metastases from RCC in our institution. The first represents the only reported metachronous ureteric deposit on adjuvant sorafenib after laparoscopic radical nephrectomy for RCC. The other presented with a synchronous lesion after radiological work-up. Both lesions were treated with endoscopic excision and laser ablation with preservation of the renal unit and no local recurrence. We report these cases and discuss the literature.